Shifting boundaries: The challenge of assessing MTech community-based-visual arts research projects - Berman, K (South African Journal of Higher Education, 2011)
This article aims to interrogate possible assessment problems arising from a community-based-research mode of research and consider some of the assessment approaches that generate scepticism among some examiners, and endorsement from others. The article explores specific challenges in supervising, accommodating and evaluating diverse candidates who pursue an action-led and community-based research approach rooted within the visual arts. I contend that there is a specific challenge in the field of postgraduate supervision of engaging evaluation strategies. If students within higher education adopt a focus towards the development of social responsibility, this would imply that the general criteria for this manner of research would require deep revision in order to accommodate diverse and direct action-based community engagement. Research in this mode embraces a multi-disciplinary approach and is therefore complex. It needs to accommodate practice, action and experience, and not be limited to traditional discipline-specific methodologies.